Improving the color deviation of white light emitting diode by employing Sr3Ga2Ge4O14:Cr3+ phosphor - Ha Thanh Tung; Huu Phuc Dang; Dieu An Nguyen Thi (Bulletin of Electrical Engineering and Informatics, 2023)
The pomising uses of near infrared (NIR) phosphor converted light emitting diodes (pc-LEDs), including non-destructive testing and biological implementations, are endless. It is still difficult to create wideband and NIR phosphors with sufficient heating steadiness for a variety of uses. The study herein introduces the phosphor Sr3Ga2Ge4O14:Cr3+, its creation procedure through expreiments as well as its influneces on LED devices. The Sr3Ga2Ge4O14:Cr3+ (SGGO:Cr3+) super-wideband NIR phosphor was effectively synthesized in this study with 431 nm stimulation, and a spectrum adjustment 750 nm-900 nm was made in a two-step superwideband radiation having its full width under half maximum (FWHM) changing among 257 and 336 nm. The inner quantum performance (IQP) for SGGO:0.15Cr3+ is 36.67%, and it has an FWHM of 257 nm. At 423 K, the emitting strength was still 76% of ambient temperature. The potential of SGGO:Cr3+ for various uses was eventually demonstrated by the employment of SGGO:0.03Cr3+ as well as SGGO:0.15Cr3+ samples accompanied by blue illumination chips under 430 nm for the task of creating NIR pc-LED gadgets then putting in nighttime sight, human palm puncture, flora lighting. It was shown that SGGO:Cr3+ has a wide range of use possibilities.